Energetic Ion Moments and Polytropic Index in Saturn's Magnetosphere using Cassini/MIMI Measurements: A Simple Model Based on κ‐Distribution Functions. Issue 10 (2nd October 2018) - Dialynas, Konstantinos; Roussos, Elias; Regoli, Leonardo; Paranicas, Christopher P.; Krimigis, Stamatios M.; Kane, Mark; Mitchell, Donald G.; Hamilton, Douglas C.; Krupp, Norbert; Carbary, James F.
Abstract: Moments of the charged particle distribution function provide a compact way of studying the transport, acceleration, and interactions of plasma and energetic particles in the magnetosphere. We employ κ ‐distributions to describe the energy spectra of H + and O +, based on >20 keV measurements by the three detectors of Cassini's Magnetospheric Imaging Instrument, covering the time period from DOY 183/2004 to 016/2016, 5 < L < 20. From the analytical spectra we calculate the equatorial distributions of energetic ion moments inside Saturn's magnetosphere and then focus on the distributions of the characteristic energy ( E c = I E / I n ), temperature, and κ ‐index of these ions. A semiempirical model is utilized to simulate the equatorial ion moments in both local time and L‐shell, allowing the derivation of the polytropic index (Γ) for both H + and O + . Primary results are as follows: (a) The ∼9 < L < 20 region corresponds to a local equatorial acceleration region, where subadiabatic transport of H + (Γ∼1.25) and quasi‐isothermal behavior of O + (Γ∼0.95) dominate the ion energetics; (b) energetic ions are heavily depleted in the inner magnetospheric regions, and their behavior appears to be quasi‐isothermal (Γ<1); (c) the (quasi‐) periodic energetic ion injections in the outer parts of Saturn's magnetosphere (especially beyond 17–18 R S ) produce durable signatures in the energetic ion moments; (d) the plasma sheet does not seem to have a ground thermodynamic state, but the extended neutral gas distribution at Saturn provides an effective cooling mechanism that does not allow the plasma sheet to behave adiabatically. Key Points: Derivation of energetic ion moments, κ ‐index, characteristic energy, temperature, and polytropic index in Saturn's magnetosphere Presentation of a semiempirical analytical model for the 20 keV energetic ion Pressure, density, and temperature The neutral gas at Saturn provides an effective cooling mechanism and does not allow the plasma sheet to behave adiabatically